Pulsed Electric Discharge in Active Metallic Grains for Water Purification Processes; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Danilenko N. B. Nina Borisovna; Yurmazova T. A. Tatyana Aleksandrovna; Tran Tuan Hoang; Nguyen Tuan Anh (2015, 2015)
Title screen